Cover, Content, and Editorial Note from Borneo J Pharm Vol. 4 No. 3 August 2021 - Chief Editor of Borneo J Pharm (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Assalamu’alaikum Wr. Wb. Alhamdulillahirabbil ‘alamin. The next edition of Borneo Journal of Pharmacy (Borneo J Pharm), has been published in August 2021. Starting from this volume, Borneo J Pharm increases the frequency of publishing four times a year. This change aims to improve the circulation of the best articles published by Borneo J Pharm. This edition contains ten articles consisting of Pharmacology-Toxicology, Microbiology Pharmacy, Natural Product Development, Clinical-Community Pharmacy, and Management Pharmacy. This edition includes writings from four countries including Greece, Indonesia, Saudi Arabia, and Sudan. The authors come from several institutions, including STIKES Cendekia Utama Kudus, Universitas Sari Mulia, National Agency of Drug and Food Control of Republic of Indonesia, National Agency of Drug and Food Control of Republic of Indonesia in Gorontalo, Universitas Muhammadiyah Kalimantan Timur, Balai Taman Nasional Gunung Merapi, Universitas Sembilanbelas November Kolaka, Sekolah Tinggi Ilmu Farmasi Riau, Omdurman Islamic University, University of Khartoum, King Saud University, Indonesian Institute of Sciences, Universitas Pancasila, Universitas Lambung Mangkurat, Universitas Jenderal Achmad Yani, Ibrahim Adjie Health Center, University of Crete, Aristotle University of Thessaloniki, New York College, Universitas Islam Sultan Agung, Sekolah Tinggi Ilmu Kesehatan Borneo Lestari, and Universitas Muhammadiyah Surakarta. The editorial board would like to thank all editors and reviewers, and contributors of the scientific articles who have provided the repertoire in this issue. We hope that all parties, especially the contributors, could re-participate for publication in the next edition in November 2021. Wassalamu’alaikum Wr. Wb.